Kajian Sastra Perjalanan dalam Hikayat Kisah Pelayaran Abdullah ke Mekah Karya Abdullah Bin Abdul Kadir Munsyi - Yacub Fahmilda; Putri Zulikha (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
This research is aimed to identify and to reveal a hikayat as classic travel literature of Indonesia by the travel writing theory of Carl Thompson. To gain those purposes, this research used literary criticism and descriptive-analytic methods. The object of this study is Kisah Pelayaran Abdullah ke Mekah by Abdullah bin Abdul Kadir Munsyi (1854), focusing on the six elements of travel writing by Carl Thompson’s approach based on the hikayat. This study shows that the hikayat contains six elements of travel writing. Those are self, other, movement, space, encounter, and writing. Abdullah as a sailor puts himself in his hikayat as the main character by using “sahaya” and “aku” to articulate “self” in his hikayat. The “self” during travel met new and foreign things that the author had never seen before. He drew and expressed his point of view, feeling, and observation of all the encounters that he had met during sailing in to hikayat.Keywords: Carl Thompson, hikayat, travel writing